The beckoning world : a novel - Bauer, Douglas (University of Iowa Press, 2022)
"The Beckoning World is set in the first quarter of the twentieth century, and follows Earl Dunham from the age of twelve to his early fifties. We meet him as a boy about to flee his abusive coal miner-father, for a life in the world, the beckoning world, which he's sure - and it's the only thing he's sure of -- will take him lyrically away from the one in which he's lived. And so, having fled, he traces the Midwest's bituminous seams, resuming the work he's known, his weeks comprised of six days mining coal and, from early spring until sometime in late fall, Sundays in the light, playing baseball. Camp teams, pick-up games, all that matters to Earl is that he plays, that he pitches, and gets ever better at it. Until, a day of high serendipity, a major-league scout happens on a game, signs Earl to a contract and he begins a life, a dream he'd had no idea was a life a man could dream. But dreams sometimes suffer from a lovely abundance, and in Earl's case her name is Emily Marchand. She's a dreamer in her own right, but of a vastly different sort, a beautiful young woman who's also set out on an adventure, one that's both like and unlike his, to "learn some things about the world". When she meets Earl she soon discovers that the world she wants to learn about is him. Their love is quickly deep, and coming with it are heartbreaking complications that make its growth, its textured world, appear impossible"--